Neuropeptide proctolin (H-Arg-Tyr-Leu-Pro-Thr-OH): immunological detection and neuronal localization in insect central nervous system. - Bishop, C A (1981)
Proctolin (H-Arg-Tyr-Leu-Pro-Thr-OH) is a pentapeptide first extracted from cockroaches. It is known to have many neurohormonal effects and has been associated with specific, identified cockroach neurons. We have produced proctolin antisera and report here on their application in detecting proctolin-like immunoreactivity (PLI) in the cockroach central nervous system. Radioimmunoassay, capable of detectable 50 fmol of proctolin, was used to quantify the distribution of PLI. Highest concentrations were detected in the genital ganglia and lowest in the cerebral ganglia. Immunohistochemistry on the cockroach central nervous system demonstrated that PLI is localized to neurons. Neurons stained by using immunohistochemistry were widespread in the ganglia. Cell bodies were found to be in constant positions from animal to animal and to occur in bilaterally symmetrical pairs. These neurons are potentially identifiable.